Salt-Regulated Accumulation of the Compatible Solutes Sucrose and Glucosylglycerol in Cyanobacteria and Its Biotechnological Potential - Kirsch, Friedrich; Klähn, Stephan; Hagemann, Martin (Frontiers in Microbiology, 2019)
Cyanobacteria are prokaryotes that can assimilate inorganic carbon via oxygenic photosynthesis, which results in the formation of organic compounds essentially from CO2, water and light. Increasing concerns regarding the increase in atmospheric CO2 due to fossil energy usage fueled the idea of a photosynthesis-driven and CO2-neutral, i.e. cyanobacteria-based biotechnology. The ability of various cyanobacteria to tolerate high and/or fluctuating salinities attenuates the requirement of freshwater for their cultivation, which makes these organisms even more interesting regarding a sustainable utilization of natural resources. However, those applications require a detailed knowledge of the processes involved in salt acclimation. Here, we review the current state of our knowledge on the regulation of compatible solute accumulation in cyanobacteria. The model organism Synechocystis sp. PCC 6803 responds to increasing salinities mainly by the accumulation of glucosylglycerol (GG) and sucrose. After exposure towards increased salt concentrations, the accumulation of the main compatible solute GG is achieved by de novo synthesis. The key target of regulation is the enzyme GG-phosphate synthase (GgpS) and involves transcriptional, posttranscriptional and biochemical mechanisms. Recently, the GG-degrading enzyme GG hydrolase A (GghA) was identified, which is particularly important for GG degradation during exposure to decreasing salinities. The inversely ion-regulated activities of GgpS and GghA could represent the main model for effectively tuning GG steady-state levels according to external salinities. Similar to GG, the intracellular amount of sucrose is also salt-regulated and seems to be determined by the balance of sucrose synthesis via sucrose-phosphate synthase (Sps) and its degradation via invertase (Inv). In addition to their role as stress protectants, both compatible solutes also represent promising targets for biotechnology. Hence, the increasing knowledge on the regulation of compatible solute accumulation not only improves our understanding of the stress physiology of cyanobacteria but will also support their future biotechnological applications.